Photoelectron Photoion Coincidence Spectroscopy of NCl3 and NCl2. Issue 21 (26th August 2021) - Gerlach, Marius; Monninger, Sophie; Schleier, Domenik; Hemberger, Patrick; Goettel, James T.; Braunschweig, Holger; Fischer, Ingo
Abstract: We investigate NCl3 and the NCl2 radical by photoelectron‐photoion coincidence spectroscopy using synchrotron radiation. The mass selected threshold photoelectron spectrum (ms‐TPES) of NCl3 is broad and unstructured due to the large geometry change. An ionization energy of 9.7±0.1 eV is estimated from the spectrum and supported by computations. NCl2 is generated by photolysis at 213 nm from NCl3 and its ms‐TPES shows an extended vibrational progression with a 90 meV spacing that is assigned to the symmetric N−Cl stretching mode in the cation. An adiabatic ionization energy of 9.94 ± 0.02 eV is determined. Abstract : An ion mass‐selected threshold photoelectron spectrum of NCl2 is reported. An ionization energy of 9.94±0.02 eV is derived from the spectrum. A vibrational progression in the symmetric stretching mode with ν1 =730 cm −1 indicates a significant decrease in the N−Cl bond length.